Education Service Delivery in Tanzania - World Bank Group (World Bank, Washington, DC, 2016)
The Service Delivery Indicators (SDI) provide a set of metrics for benchmarking service delivery performance in education and health. The overall objective of the indicators is to gauge the quality of service delivery in primary education and basic health services. The indicators enable the identification of gaps and tracking of progress over time and across countries. It is envisaged that the broad availability, high public awareness and a persistent focus on the indicators will mobilize policymakers, citizens, service providers, donors and other stakeholders for action to improve the quality of services and ultimately to improve development outcomes and social welfare. This report presents the findings from the implementation of the Service Delivery Indicators in the Education sector in Tanzania in 2014. Survey implementation was preceded by an extensive consultation with Government and key stakeholders on survey design, sampling, and adaptation of survey instruments. Pre-testing of the survey instruments, enumerator training, and fieldwork took place in 2014. In conclusion, comparing the 2010 and 2014 SDI surveys, one clearly notices that Tanzania has made substantial progress in some areas, but there are still remaining gaps. Also, the achieved progress is from a very low base and there is still quite a bit of room for the Tanzanian education system to deliver quality to its pupils and get them prepared and equipped to face competition in the national, regional, and international labor markets.